The law in Nazi Germany : ideology, opportunism, and the perversion of justice - Steinweis, Alan E.; Rachlin, Robert D. (Vermont studies on Nazi Germany and the Holocaust., 2013)
"While we often tend to think of the Third Reich as a zone of lawlessness, the Nazi dictatorship and its policies of persecution rested on a legal foundation set in place and maintained by judges, lawyers, and civil servants trained in the law. This volume offers a concise and compelling account of how these intelligent and well-educated legal professionals lent their skills and knowledge to a system of oppression and domination. The chapters address why German lawyers and jurists were attracted to Nazism; how their support of the regime resulted from a combination of ideological conviction, careerist opportunism, and legalistic self-delusion; and whether they were held accountable for their Nazi-era actions after 1945. This book also examines the experiences of Jewish lawyers who fell victim to anti-Semitic measures. The volume will appeal to scholars, students, and other readers with an interest in Nazi Germany, the Holocaust, and the history of jurisprudence"--Provided by publisher.